W kierunku usprawniania i zobiektywizowania metod konsultacji i partycypacji społecznej w projektach miejskich. Przykłady Rzeszowa i Kielc - Malikowski, Marian; Malikowski, Radosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The purpose of this paper is to describe the urban participation project which are more and more popular in the core countries that founded European Union. This kind of social activity starting to be more common in Poland as well. It is generally connected with democratization and in this case with wide participation of urban society (average citizens of cities and subdivisions). In includes whole processe as cities revitalization, urban renewal and redevelopment as well as transformation social and cultural life of urban community. The aim of this article is to show the advantages and disadvantages, barriers and benefition in the Rzeszow and Kielce cities.
Keywords: urban projects; social participation; co-housing; deliberative polling